Association between serum uric acid to high-density lipoprotein cholesterol ratio (UHR) and abdominal aortic calcification: a cross-sectional study based on NHANES 2013–2014 - Bowen Li; Yue Xu; Qingwei He; Qiaoxiang Yin; Mengdi Wu; Huijing Zhu; Yanjie Cao (Frontiers in Cardiovascular Medicine)
BackgroundCardiovascular diseases (CVDs) are among the leading causes of mortality worldwide, with abdominal aortic calcification (AAC) being an independent risk factor. The serum uric acid (sUA) to high-density lipoprotein cholesterol (HDL-C) ratio (UHR) integrates both pro-atherogenic (sUA-induced endothelial dysfunction) and anti-atherogenic factors (HDL-C-mediated cholesterol efflux), which may be associated with vascular calcification. However, epidemiological evidence on their relationship remains scarce.MethodsThis cross-sectional study analyzed data from 2,789 U.S. adults aged ≥40 years in the National Health and Nutrition Examination Survey (NHANES) 2013–2014 with complete AAC and UHR data. Participants with invalid AAC imaging, missing sUA/HDL-C measurements, or incomplete calcium/phosphorus intake records were excluded. AAC severity was quantified using the Kauppila scoring system via dual-energy x-ray absorptiometry. UHR was calculated as [sUA [mg/dl] divided by HDL-C [mg/dl]] multiplied by 100. Weighted multivariable linear and logistic regression models assessed associations, while weighted restricted cubic splines explored nonlinear relationships. Subgroup analyses and sensitivity analyses assessed the robustness of findings.ResultsThe study included a total of 2,789 participants aged 40 or older. After multifactorial adjustment, the regression model indicated that a higher UHR was significantly associated with increased AAC scores (β = 1.055, 95%CI: 1.024–1.087), AAC (OR = 2.605, 95%CI:1.760–3.855), and severe AAC (OR = 2.227, 95%CI:1.649–3.008). The restricted cubic spline analysis revealed significant nonlinear relationships between UHR and both AAC scores and AAC, presenting an inverted “L” shape, with the risk rising sharply at UHR levels close to 17.8–18.0 and then plateauing. Subgroup analyses suggested potential interactions between gender and diabetes in the UHR-AAC association, while sensitivity analyses confirmed the stability of the findings.ConclusionIn a U.S. middle-aged and elderly population, the UHR was found to be nonlinearly associated with the risk of AAC, and may interact with gender and diabetes. However, due to the cross-sectional design, no causal inferences can be drawn. Future longitudinal studies may be considered to validate these associations and explore whether interventions targeting UHR could potentially slow down the progression of vascular calcification.